2010
DOI: 10.3324/haematol.2009.019778
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-induced side effects are not due to differences in pharmacokinetics in children with Down syndrome and acute lymphoblastic leukemia

Abstract: BackgroundChildren with Down syndrome have an increased risk of developing acute lymphoblastic leukemia and a poor tolerance of methotrexate. This latter problem is assumed to be caused by a higher cellular sensitivity of tissues in children with Down syndrome. However, whether differences in pharmacokinetics play a role is unknown. Design and MethodsWe compared methotrexate-induced toxicity and pharmacokinetics in a retrospective casecontrol study between patients with acute lymphoblastic leukemia who did or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 40 publications
8
67
1
3
Order By: Relevance
“…Of the 1883 patients treated with HDMTX on P9904 and P9905, 1588 were eligible and had germline DNA evaluable. 6 Patients who had congenital abnormalities (usually Down syndrome, which is known to affect methotrexate clearance) [13][14][15] or who did not have any courses that passed methotrexate quality control were excluded ( Figure 1). Demographic information on the patients included can be found in supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 1883 patients treated with HDMTX on P9904 and P9905, 1588 were eligible and had germline DNA evaluable. 6 Patients who had congenital abnormalities (usually Down syndrome, which is known to affect methotrexate clearance) [13][14][15] or who did not have any courses that passed methotrexate quality control were excluded ( Figure 1). Demographic information on the patients included can be found in supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The report by Buitenkamp et al in this issue of the Journal addresses whether differences in pharmacokinetics could account for differences in drug sensitivity and toxicity seen in children with Down syndrome and ALL. 33 Methotrexate pharmacokinetics were analyzed retrospectively in children with ALL, comparing 44 with Down syndrome and 87 without the syndrome. 33 Using non-linear mixed effect modeling, no differences in methotrexate pharmacokinetics were found between patients with and without Down syndrome which could explain the significantly higher proportion of children with Down syndrome who experienced methotrexate-induced gastrointestinal toxicity.…”
mentioning
confidence: 99%
“…33 Methotrexate pharmacokinetics were analyzed retrospectively in children with ALL, comparing 44 with Down syndrome and 87 without the syndrome. 33 Using non-linear mixed effect modeling, no differences in methotrexate pharmacokinetics were found between patients with and without Down syndrome which could explain the significantly higher proportion of children with Down syndrome who experienced methotrexate-induced gastrointestinal toxicity. The authors concluded that the higher toxicities suffered by Down syndrome patients are probably related to pharmacodynamic differences of the gastrointestinal mucosa and that intermediate doses of methotrexate (such as 1-3 g/m 2 ) can be used safely in Down syndrome children with ALL.…”
mentioning
confidence: 99%
“…The authors concluded that the higher toxicities suffered by Down syndrome patients are probably related to pharmacodynamic differences and that intermediate doses of methotrexate (such as 1-3 g/ m 2 ) can be used safely in Down syndrome children with ALL [7].…”
Section: Discussionmentioning
confidence: 99%